MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS MAHASISWA PROGRAM STUDI D2 BAHASA PERANCIS FKIP-UNILA MELALUI ROLE PLAY - Flora Flora (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2014)
The aims of this classroom action research are (1) to find out whether role play can increase students ’ participation in teaching-learning process and (2) to find out whether it can increase students ’ ability in speaking. The data collected in this research were both qualitative and quantitative. The qualitative data were used to find out the students ’ participation while the quantitative data were used to determine the students ’ ability in speaking. The indicators of the success of this research were (1) that the students are 100% active during the teaching-learning process and (2) that at least 85% of the students get the minimum score of 70. In the first cycle, only 9 students (56%) who take participation, while the percentage of students who get the minimum score of 70 is 4 students (25%). In the second cycle, the percentage of students who take participation is 16 students (100%) and the percentage of students who get the minimum score of 70 is 8 students (50%). In the last cycle, the third cycle, it was gained that the percentage of students who take participation is 100% and the percentage of students who get the minimum score of 70 is 14 students (87.75%). In other words, the target of this research has been achieved at the end of the third cycle.